Preparation method and application of biochar co-pyrolysis ceramsite based on waste
Through the waste-based biochar copyrolytic ceramic preparation method, high-porosity ceramics are formed by using magnesium-modified peanut shells, bauxite and coal gangue, which solves the poor interception effect of existing water interceptor fillers. The problem of this problem has achieved efficient and low-cost nitrogen and phosphorus interception effect.
Patent Information
- Application Number
- CN202411290624.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing water intercepting fillers have poor intercepting effects on nitrogen and phosphorus pollutants, mainly due to the lack of protruding surface pore structure and fewer adsorption points, resulting in a general interception effect.
Using waste-based biochar copyrolytic ceramate preparation method, the combination of materials such as magnesium modified peanut shells, bauxite and coal gangue is formed to form ceramic products with high porosity, good consolidation and strong durability. , the network structure of magnesium oxide and biochar is used to increase the adsorption point and improve the interception ability of nitrogen and phosphorus.
It significantly improves the interception effect of nitrogen and phosphorus, and the cost is only 1/3-1/2 of similar products. It has a simple process and low reagent prices, reducing waste of chemical reagents and environmental pollution.
Smart Images

Figure CN119143475A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adsorption materials and relates to a method for preparing waste-based biochar co-pyrolysis ceramsite and applications thereof. Background Art
[0002] Nitrogen and phosphorus are the most important limiting factors for the growth of plants and crops. At the same time, point and non-point source pollution such as agricultural fertilization, industrial production, livestock and poultry breeding, and residents' lives produce a large amount of nitrogen and phosphorus-containing wastewater, some of which are directly or indirectly discharged into rivers, lakes, reservoirs, and seawater without treatment. They are important growth limiting factors for algae in rivers and lakes, and are also important inducements for eutrophication of water bodies, which can then cause ecological disasters such as algal blooms and blue algae outbreaks. A typical case is the Taihu blue algae incident in 2007. Therefore, my country's "Surface Water Environmental Quality Standards" set the water quality standards for ammonia nitrogen, total nitrogen, and total phosphorus as 2.0, 2.0, and 0.4 mg / L (Class V water) respectively, in order to control the input of nitrogen and phosphorus nutrients in surface water bodies into lakes and reservoirs. Therefore, controlling nitrogen and phosphorus in water bodies is of great significance for controlling water environment improvement, water eutrophication control, and the health of aquatic ecosystems.
[0003] The resource utilization of agricultural waste is an important task in the construction of ecological civilization in my country. However, the current traditional resource utilization methods such as natural decomposition and incineration will produce greenhouse gas emissions and water and soil pollution. Therefore, the reasonable and efficient realization of the resource utilization of agricultural waste is of great practical significance for achieving energy conservation, emission reduction and environmental pollution control.
[0004] Coal gangue is a common solid waste screened during coal mining and coal washing. Its main components include aluminum oxide, silicon oxide and carbon, and it has a certain combustion value. my country's annual emission is huge. According to statistics, the annual emission accounts for about 10% of the total coal production. The generation of coal gangue can cause a large number of incidental environmental problems, such as large-scale occupation of land resources, health threats caused by dust, leakage or leaching of harmful substances, etc. Therefore, the effective use of coal gangue is also of great significance for the efficient and rational use of resources.
[0005] At present, the main interception fillers for pollutants in water bodies are zeolite, aerated concrete, volcanic rock, etc., which mainly rely on their own rich pore structure and adsorption points to achieve physical or chemical adsorption of nitrogen and phosphorus. However, the interception effect of the above interception fillers is relatively general. The main reasons are: the pore structure on the surface of the above fillers is not prominent. Another important reason is that there are fewer adsorption points that combine with pollutants.
[0006] Ceramic granules are one of the fastest growing environmentally friendly materials in my country. They are small in size, rich in pore size, and high in adsorption efficiency. Ceramic granules in general water treatment are lightweight spheres formed by crushing, pelletizing, drying, and high-temperature calcining of some industrial waste (slag, fly ash, and mineral materials). They play an important role in intercepting pollutants in water pollution treatment. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing ceramsite by co-pyrolysis of biochar based on waste and its application. Waste is applied to the preparation of ceramsite, and a ceramsite product with large porosity, high consolidation, good durability and outstanding barrier control effect is prepared by improving the process and adding key components.
[0008] The first aspect of the present invention provides a method for preparing waste-based biochar co-pyrolysis ceramsite, comprising the following steps:
[0009] Preparation of magnesium-modified peanut shells: using a magnesium salt solution to spray and modify the crushed peanut shells, and then adding a KOH solution to treat, to obtain magnesium-modified peanut shells;
[0010] Preparation of waste-based biochar co-pyrolysis ceramsite: magnesium-modified peanut shells, potassium bicarbonate and water are mixed, and granulated into balls by adding bauxite and coal gangue. After the balls are formed, they are aged and preheated at 300°C-400°C for 0.5h-1.5h; after the preheating is completed, they are continuously calcined at 500°C-700°C for 0.5h-1.5h, and cooled to form waste-based biochar co-pyrolysis ceramsite;
[0011] The mass ratio of magnesium-modified peanut shell, bauxite, coal gangue, potassium bicarbonate and water is 0.1:(0.5-1.5):(1.5-2.5):(0.04-0.06):(0.3-0.4);
[0012] The total added molar ratio of magnesium ions in the magnesium salt solution and hydroxide ions in the KOH solution is: 1:(2.3-2.7).
[0013] In a preferred embodiment, during the preparation of magnesium-modified peanut shells, the crushed peanut shells are sieved, and the peanut shells are sprayed with a 0.2-1.5 mol / L magnesium salt solution so that the surface of the peanut shells is evenly moistened with the magnesium salt solution. After standing for 18-28 hours (preferably 24 hours), the peanut shells are evenly sprayed with a 1-2 mol / L KOH solution, and then stirred to mix.
[0014] Furthermore, the total addition molar ratio of magnesium ions in the magnesium salt solution and hydroxide ions in the KOH solution is 1:2.5; and the magnesium salt is MgCl2.
[0015] In a preferred embodiment, magnesium modification and pyrolysis are performed to cause the pores of peanut shells to swell and form nano-sized magnesium oxide MgO.
[0016] In a preferred embodiment, during preheating, potassium bicarbonate decomposes to produce a large amount of CO2 to form a porous structure, and the magnesium-modified peanut shells begin to gradually pyrolyze to form biochar; during calcination, the coal gangue pyrolyzes to form a porous structure, bauxite recrystallizes to form a hardened skeleton, the peanut shells pyrolyze to form biochar with rich pores, and the Mg(OH)2 formed by co-precipitation pyrolyzes to form rich MgO binding sites.
[0017] Furthermore, the diameter of the pellets is 2-3 cm, and the pelletizing time is 20-40 min. The specific surface area is >5.0 m 2 / g, porosity>53%.
[0018] The second aspect of the present invention is to disclose the waste-based biochar co-pyrolysis ceramsite prepared by the aforementioned preparation method.
[0019] The third aspect of the present invention is to provide an interception dam filled with the aforementioned waste-based biochar co-pyrolysis ceramsite.
[0020] Furthermore, the interception dam is used to intercept or absorb nitrogen and phosphorus in farmland runoff during fertilization periods and / or rainstorm periods.
[0021] The fourth aspect of the present invention is to disclose the application of the aforementioned preparation method or the aforementioned waste-based biochar co-pyrolysis ceramsite in intercepting or adsorbing nitrogen and phosphorus in farmland runoff water.
[0022] Compared with the prior art, the present invention has the following significant advantages:
[0023] The biochar co-pyrolysis ceramsite production process of the present invention is simple and convenient, wherein reagents such as MgCl2 and KOH are inexpensive, and KOH and MgCl2 are preferably used as spraying reagents. Compared with alkaline reagents such as NaOH, the purpose of selecting KOH is mainly because the residual K, as the main essential element for crops, can promote the growth of crops; compared with Mg(NO3)2, the main purpose of selecting MgCl2 is that it has a significant price advantage. On the other hand, the residual metal chloride is easier to decompose than oxides and sulfides.
[0024] More importantly, the spray wetting process can effectively save the chemical reagents used, reduce the reagent waste caused by the solution impregnation method or the solution co-precipitation method, and reduce the environmental problems and manufacturing costs caused by the reagent treatment.
[0025] According to the spraying ratio of 1:2.5, Mg 2+ With OH -Theoretically, the concentration ratio of the two reactions is 1:2. However, since the two are sprayed alternately (MgCl2 is sprayed first, and then KOH is sprayed, which is conducive to the formation of MgO) to achieve surface co-precipitation reaction, there may be Mg 2+ In the case of incomplete reaction, therefore, sufficient OH needs to be provided - Used to make the above coprecipitation reaction complete. After optimization experiments, the applicant of the present invention found that a ratio of 1:2.5 (molar ratio) (i.e., sufficient KOH) can promote the complete reaction, thereby promoting the formation of Mg(OH)2 products cross-linked inside the peanut shell. The Mg(OH)2 formed by the modification process of MgCl2 and KOH (or MgO formed by pyrolysis) can increase the number of surface adsorption sites of ceramsite and improve the retention capacity of pollutants.
[0026] The metal loading, agricultural waste raw materials and their addition amount of this product are determined through a large number of experiments. After analyzing different metal loadings (Mg, Fe, Ca, La), as well as agricultural waste such as wheat straw, rice straw, peanut shells, corn cobs, yellow calamus, water hyacinth, poplar sawdust and coffee grounds, through cross-validation analysis, it was concluded that peanut shell loading Mg can achieve the maximum nitrogen and phosphorus adsorption. The peanut shell material buried underground is loose and breathable, with rich pores, and has an interconnected pore structure that is difficult for other biological wastes to have. Through Mg modification, widely distributed Mg oxide components can be formed in its pores during pyrolysis. These Mg oxide components formed in the pores have also been shown to form nano-scale MgO structures through swelling, thereby expanding the original pores of the peanut shell (that is, MgO and water vapor formed by pyrolysis of Mg(OH)2 can expand the channels of biochar and promote the cross-linking structure of its pores); Mg oxide is an important adsorption site in the water environment and can adsorb pollutants such as nitrate nitrogen and phosphate. After preheating and high-temperature pyrolysis, the network structure formed by peanut shell biochar and MgO, coal gangue, and potassium bicarbonate has a higher nitrogen and phosphorus binding capacity than traditional expanded clay.
[0027] my country is rich in bauxite resources and has outstanding price advantages. In addition, Al2O3 in bauxite can form crystalline components under high temperature conditions, which can improve the compressive strength and durability of ceramsite, provide basic rigidity characteristics of ceramsite, and prevent the material from being dispersed in water. Coal gangue has a certain combustion value, and its carbon content is about 14.07%, which can effectively save energy and realize the efficient utilization of coal mining waste. The organic matter components can form a cross-linked pore structure after combustion, which can also increase the pollutant interception ability of ceramsite, and the calcium-silicon-aluminum-magnesium structure in coal gangue can become an effective structure for constructing the skeleton of ceramsite. The combination of bauxite and coal gangue can increase the hardness of ceramsite, and modified peanut shells and coal gangue can increase the pore structure of ceramsite. A certain ratio must be controlled between bauxite, coal gangue and modified peanut shells. Among them, too high coal gangue content may make it difficult to meet the hardness of the expanded clay, while too low a content may result in insufficient porosity. Too high a bauxite content may lead to excessively high costs, while too high a modified peanut shell content may lead to excessively high costs, while too low a porosity may make it difficult to meet the standards.
[0028] Potassium bicarbonate, as a foaming agent, produces a large amount of CO2 and H2O (gaseous) during the preheating stage, which can effectively produce a porous structure, thereby increasing the specific surface area of ceramsite. The preheating process is 300℃-400℃ for 0.5h-1.5h. This temperature can promote the decomposition of potassium bicarbonate to form CO2 and H2O (gaseous). The formation process and release of CO2 and water vapor can promote the formation of a rich pore structure, and can assist in promoting the formation of a network cross-linked structure formed by the pyrolysis of coal gangue and modified biochar during calcination; too high a preheating temperature will increase the preparation cost of ceramsite.
[0029] The calcination temperature of ceramsite is 500℃-700℃. At this temperature, bauxite begins to decompose, dehydrate and recrystallize to form a hardened ceramsite skeleton. Biochar completes high pyrolysis and forms a rich MgO structure. Too high a temperature may cause the cross-linked pore structure of biochar to begin to collapse, but too low a pyrolysis temperature may make it difficult for bauxite to dehydrate and decompose, weakening its rigidity.
[0030] The ceramsite of the present invention has a nitrogen and phosphorus interception effect that is not lower than that of similar ceramsites, while the cost is only about 1 / 3 to 1 / 2 of that of similar products. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Adsorption isotherms of (a) nitrate and (b) phosphate on ceramsite under different preparation strategies;
[0032] Figure 2 SEM images of ceramsite 8 and ceramsite 1;
[0033] Figure 3 BET specific surface area distribution diagram, A, ceramsite without magnesium loading, B, ceramsite loaded with magnesium;
[0034] Figure 4 The pore volume and specific surface area of ceramsite, a and b correspond to Example 1, c and d correspond to Example 2, and e and f correspond to Example 9;
[0035] Figure 5 The interception rates of different interception fillers for (a) nitrate and (b) phosphate (where 1-5 are common zeolite, common ceramsite, Example 8, Example 9, and Example 1, respectively). DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0037] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, instruments, etc. used in the following examples are all commercially available unless otherwise specified.
[0038] Example 1
[0039] The crushed peanut shells were sieved through a 60-mesh sieve, and the peanut shells were sprayed with a 0.5 mol / L MgCl2 solution at a spraying rate of 0.1 L / (h*kg) (i.e., 0.1 L MgCl2 solution was sprayed per kg of crushed peanut shells per hour), and the spraying time was 10 min. A stirring device was used for mixing and stirring (200 rpm) while spraying. The spraying method depends on the actual preparation scenario, and the surface of the peanut shells can be wetted. After standing overnight, a 1.25 mol / L KOH solution was used to spray evenly according to the same steps as spraying MgCl2. The stirring speed, spraying speed and spraying time were consistent with the steps of spraying MgCl2. The two reagents were sprayed alternately twice, and a stirrer was used to stir (200 rpm) for 1-2 hours. Take out the magnesium-modified peanut shells and dry them for later use.
[0040] Preparation of waste-based biochar co-pyrolysis ceramsite:
[0041] After the different components are crushed, magnesium-modified peanut shells and potassium bicarbonate are first mixed, and then mixed with bauxite and coal gangue. The mixture is mixed in a mass ratio of 1:2:0.1:0.05 of bauxite, coal gangue, magnesium-modified peanut shells and potassium bicarbonate. After grinding, water (10%, referring to the mass percentage of the mixture of water, bauxite, coal gangue, magnesium-modified peanut shells and potassium bicarbonate) is added and mixed. Then, a disc ball making machine is used to make balls with a diameter of about 2-3 cm, a ball forming time of 30 minutes, and a standing aging for 24 hours. Then, the preheating temperature is 350°C for 1 hour, calcined (600°C for 1 hour), and the required ceramsite 1 (PS-600-C-Mg) is obtained after cooling.
[0042] Embodiment 2:
[0043] The preparation method is similar to that of Example 1, except that the raw material is rice straw, and the product is recorded as RS-600-C-Mg.
[0044] Embodiment 3:
[0045] The preparation method is similar to that of Example 1, except that the calcination temperature is 400 degrees Celsius, and the product is recorded as PS-400-C-Mg.
[0046] Embodiment 4:
[0047] The preparation method is similar to that of Example 1, except that there is no KOH spraying process, and the product is recorded as PS-600-I-Mg.
[0048] Embodiment 5:
[0049] The preparation method is similar to that of Example 1, except that the metal salt solution sprayed is ferric chloride, and the product is recorded as PS-600-C-Fe.
[0050] Embodiment 6:
[0051] The preparation method is similar to that of Example 1, except that the metal salt solution sprayed is lanthanum chloride, and the product is recorded as PS-600-C-La.
[0052] Example 7
[0053] The preparation method is similar to that of Example 1, except that the impregnation method is used to prepare the relevant modified Mg biochar.
[0054] Embodiment 8:
[0055] The preparation method is similar to that of Example 1, except that there is no surface modification process of magnesium oxide (ie, the peanut shell is not modified by magnesium chloride and KOH), and the product is ceramsite 8.
[0056] Embodiment 9:
[0057] The preparation method is similar to that of Example 1, except that potassium bicarbonate is not added, and the product is ceramsite 9.
[0058] Embodiment 10:
[0059] The preparation method is similar to that of Example 1, except that there is no preheating process, and the product is ceramsite 10.
[0060] By analyzing the adsorption effects of ceramsite prepared by different strategies on typical nitrates and phosphates, it can be found that the theoretical maximum adsorption capacity of ceramsite PS-600-C-Mg reached 49.63 mg / g and 59.84 mg / g, respectively, which is significantly better than that of ceramsite materials under other preparation conditions (raw materials, pyrolysis temperature, modification method, and modified metal type) (Table 1 and Figure 1 ).
[0061] Table 1 Removal efficiency of nitrogen and phosphorus by different ceramsite powders
[0062]
[0063]
[0064] The loading of metallic Mg significantly improves the purification effect of expanded clay on total phosphorus and total nitrogen. This is mainly because the main components (phosphate and nitrate) are in anionic form. The MgO component formed during the firing process can form an effective adsorption site, and its positively charged surface characteristics have extremely high adsorption efficiency for phosphate and nitrate.
[0065] Compared with the expanded clay prepared from rice straw, the expanded clay prepared from peanut shells showed a more prominent purification effect in nitrogen and phosphorus removal. This is mainly because compared with other agricultural wastes, peanut shells have an interconnected pore structure, and the fired expanded clay has a more efficient nitrogen and phosphorus interception ability.
[0066] The calcination temperature can significantly affect the hardening degree of ceramsite. The applicant found that other calcination temperatures (400° C.) could not significantly increase the interception and purification capacity of ceramsite for nitrogen and phosphorus. Therefore, the present invention uses 600° C. as the final preferred calcination temperature.
[0067] The nitrogen and phosphorus interception capacity of the expanded clay products loaded with ferric chloride and lanthanum chloride is lower than that of the expanded clay prepared by the present invention. The main reason is that the iron / lanthanum oxide particles produced by the two are larger and difficult to enter the rich pores of peanut shells, making it difficult to construct a network pore structure, resulting in a decrease in purification capacity.
[0068] Figure 2 The SEM electron microscope images of the unloaded magnesium product ceramsite 8 (a, b, corresponding to Example 8) and the ceramsite 1 loaded and fired with magnesium (c, d, corresponding to Example 1) show that the magnesium loading process effectively increases its pore structure, and the swelling process of magnesium oxide is conducive to the expansion of micropores, which can increase the adsorption capacity for nitrogen and phosphorus. The results of specific surface area ( Figure 3 ) also further verified the results of the magnesium oxide swelling process. After magnesium loading, the volume of its mesopores and macropores further increased, which is beneficial to the retention and elimination of pollutants.
[0069] Figure 4It is shown that replacing magnesium-modified peanut shell biochar with magnesium-modified rice straw biochar (Example 2) or not adding potassium bicarbonate greatly weakens the specific surface area and pore volume of ceramsite. In Example 1, the combined use of peanut shells and potassium bicarbonate can greatly increase the specific surface area of ceramsite, thereby improving the ability of ceramsite to reduce pollutants. This is mainly due to the fact that potassium bicarbonate enters the loose and porous structure of peanut shells. During the preheating stage, potassium bicarbonate acts as a foaming agent, producing a large amount of carbon dioxide gas and water vapor, which promotes the generation of pores in ceramsite. Therefore, in the invention, in the porous structure of peanut shells, combined with the "foaming agent" function of potassium bicarbonate, the pore structure of ceramsite can be effectively improved, achieving a synergistic effect of adsorption and interception effects.
[0070] Application Example 1
[0071] Place 5 products including common zeolite (green zeolite, with a diameter of 2-3 cm) and common expanded clay (bauxite expanded clay, which is made of bauxite and manganese powder after crushing and balling and then calcined to 1100 degrees Celsius by coal powder and kept for 1 hour) sold in the market, as well as Examples 8 and 9, and the biochar co-pyrolysis expanded clay 1 prepared by the present invention (corresponding to Example 1) in parallel ditches to test their ability to intercept nitrogen and phosphorus in runoff. The pollutant concentration levels in the farmland drainage water in the ditch are: total nitrogen 1.32-9.18 mg / L, total phosphorus 0.05-0.13 mg / L, ammonia nitrogen 0.25-2.58 mg / L, COD 5.5-42.1 mg / L. The filling amount of expanded clay filler is 0.03 cubic meters per mu. The changes in pollutant content in the water body before and after the interception dam are measured every 30 minutes or until the runoff ends. The final average interception rate is as follows. Figure 5 As shown, the reduction rate of total nitrogen and total phosphorus by the ceramsite of the embodiment of the present invention can reach 46.25±10.72% and 29.96±8.80%, which is much higher than other interception fillers (-2.96%-13.23% and -9.41-3.88%) ( Figure 5 ).
[0072] Application Example 2
[0073] Laboratory interception and purification experiment:
[0074] The experimental water was artificially prepared to simulate polluted water: COD 30mg / L, total nitrogen 8mg / L, ammonia nitrogen (NH4 + -N)5mg / L, total phosphorus 1mg / L.
[0075] An adsorption device was constructed in the laboratory for testing. 5 g of different test fillers in Examples 1 and 8-10 were added to 5 L of simulated wastewater. The pH was set to 7.5±0.2 at room temperature. After stirring (10 r / min) and adsorption for 24 h, the changes in the contents of different pollutants in the supernatant before and after adsorption were detected. The adsorption removal rate was calculated based on the changes. The results are shown in Table 2.
[0076] Table 2 Removal capacity of different ceramsite for nitrogen and phosphorus
[0077]
[0078]
[0079] In Examples 8 and 9, the absence of magnesium oxide and potassium bicarbonate resulted in a reduction in the surface adsorption sites and pore structure, respectively, which led to a decrease in the nitrogen and phosphorus purification capacity. In Example 10, the absence of a preheating process resulted in an incomplete reaction between MgO and water vapor, which resulted in an imperfect development of the pore cross-linked structure of the ceramsite, greatly affecting its interception effect.
[0080] Application Example 3
[0081] Actual ditch interception and purification experiment:
[0082] An interception dam filled with the above-mentioned ceramsite (Example 1) was set in an actual ditch, and its interception effect on nitrogen and phosphorus in farmland runoff during the fertilization period and the rainstorm period was monitored and analyzed. The specific location was located in the farmland interception ditch in Zhaojiatang area, Xinkang Village, Wujin District, Changzhou, my country, and the ceramsite filler filling amount was 0.03 cubic meters / mu. The change in pollutant content in the water body before and after the interception dam was measured every 30 minutes or until there was no rainfall runoff, and the final average interception efficiency was calculated. The results are as follows:
[0083] Table 3 Actual rainfall runoff interception experiment
[0084]
[0085]
[0086] The interception effect shows that with the increase of interception times, the interception effect of total nitrogen and total phosphorus gradually decreases, but the interception effect of the ceramsite of the present invention for total phosphorus is above 50%, and the interception effect of total nitrogen is also above 30%.
[0087] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for preparing biochar co-pyrolysis ceramsite based on waste, characterized in that: The steps include: Preparation of magnesium-modified peanut shells: using a magnesium salt solution to spray and modify the crushed peanut shells, and then adding a KOH solution to treat, to obtain magnesium-modified peanut shells; Preparation of waste-based biochar co-pyrolysis ceramsite: magnesium-modified peanut shells, potassium bicarbonate and water are mixed, and granulated into balls by adding bauxite and coal gangue. After the balls are formed, they are aged and preheated at 300°C-400°C for 0.5h-1.5h; after the preheating is completed, they are continuously calcined at 500°C-700°C for 0.5h-1.5h, and cooled to form waste-based biochar co-pyrolysis ceramsite; The mass ratio of magnesium-modified peanut shell, bauxite, coal gangue, potassium bicarbonate and water is 0.1:(0.5-1.5):(1.5-2.5):(0.04-0.06):(0.3-0.4); The total added molar ratio of magnesium ions in the magnesium salt solution and hydroxide ions in the KOH solution is: 1:(2.3-2.7).
2. The method for preparing waste-based biochar co-pyrolysis ceramsite according to claim 1, characterized in that: In the preparation process of magnesium-modified peanut shells, the crushed peanut shells are sieved, and the peanut shells are sprayed with a 0.2-1.5 mol / L magnesium salt solution so that the surface of the peanut shells is evenly wetted by the magnesium salt solution. After standing for 18-28 hours, the peanut shells are evenly sprayed with a 1-2 mol / L KOH solution and then stirred to mix.
3. The method for preparing waste-based biochar co-pyrolysis ceramsite according to claim 1, characterized in that: The total molar ratio of magnesium ions in the magnesium salt solution and hydroxide ions in the KOH solution is 1:2.5; the magnesium salt is MgCl2.
4. The method for preparing waste-based biochar co-pyrolysis ceramsite according to claim 1, characterized in that: Through magnesium modification and pyrolysis, the pores of peanut shells swell to form nano-scale magnesium oxide MgO.
5. The method for preparing waste-based biochar co-pyrolysis ceramsite according to claim 1, characterized in that: During preheating, magnesium-modified peanut shells begin to pyrolyze to form biochar, and potassium bicarbonate decomposes and dehydrates to form a porous structure; during calcination, coal gangue decomposes and dehydrates to form a porous structure, bauxite decomposes and dehydrates to recrystallize to form a hardened skeleton, peanut shells pyrolyze to form biochar with rich pores, and Mg(OH)2 formed by co-precipitation pyrolyzes to form a rich MgO structure.
6. The method for preparing waste-based biochar co-pyrolysis ceramsite according to claim 1, characterized in that: The ball diameter is 2-3cm, and the ball forming time is 20-40min; the specific surface area is >5.0m 2 / g, porosity>53%.
7. Waste-based biochar co-pyrolysis ceramsite obtained by the preparation method described in any one of claims 1 to 6.
8. An interception dam, characterized in that: The interception dam is filled with the waste-based biochar co-pyrolysis ceramsite as described in claim 7.
9. The interception dam according to claim 8, characterized in that: The interception dam is used to intercept or absorb nitrogen and phosphorus in the runoff from farmland during the fertilization period and / or the rainstorm period.
10. Use of the preparation method according to any one of claims 1 to 6 or the waste-based biochar co-pyrolysis ceramsite according to claim 7 in intercepting or adsorbing nitrogen and phosphorus in farmland runoff.
Citation Information
Patent Citations
Preparation of high-strength coal gangue ceramsite
CN103539480A
Metal element improved biochar-based nitrate radical adsorbent and preparation method thereof
CN104258812A
Construction method for multi-stage efficient interception and recycling of nitrogen and phosphorus pollution in farmland recession
CN111533364A
Method for preparing biochar through alkali fusion fly ash-straw co-pyrolysis and application of biochar
CN115125017A
Combined charcoal-based trace element slow-release fertilizer, preparation method and potting container
CN117466683A
